Memorial Narrative and Procedural Aspects of Cultural Exclusion - Sergey A. Troitskiy (Галактика медиа: журнал медиа исследований, 2022)
The article focuses on the process of deploying a public memorial narrative and its impact on cultural memory and the processes of cultural exclusion. The author proposes to look at several aspects using new methodological solutions: how the public memorial narrative is formed; why the narrative does not fall apart if different people participate in its deployment; how the memorial narrative preserves excluded experience; how the research of cultural memory benefits from video game study approach. The main goal is to find out how the excluded cultural experience is preserved, if the main task of deploying a public narrative is to displace the “superfluous”. Several analytical concepts are proposed: the key point, the interpretive bundle, the zero point, the descriptive bolvanka, the procedural rhetoric of cultural memory, the chronotope of the public memorial narrative and others. Through these notions it is possible to explain some processes of narrative pragmatics related to emotions, behavior, presumptions and stereotypes. The article is intended for a wide range of readers interested in public history, the history of emotions, narratology, the theory of cultural exclusion and frontier zones.